Diagnostic Accuracy of Ultrasound in Terms of Sensitivity and Specificity for Detection of Rotator Cuff Tears Keeping MRI as Gold Standard - Naseem, Nawal; Sarfraz, Saulat; Javed, Maaza; Mahmood, Hafiz Abad; Javed, Abdullah (Indus Journal of Bioscience Research, 2025)
Background: Rotator cuff tears are a common cause of shoulder pain, significantly affecting mobility and quality of life. Accurate and cost-effective diagnostic methods are essential, particularly in resource-limited settings. While MRI is considered the gold standard, the role of ultrasound in diagnosing rotator cuff tears remains under investigation, with its performance varying across different studies and populations. Objective: To determine diagnostic accuracy of ultrasound in terms of sensitivity and specificity for detection of rotator cuff tears keeping MRI as gold standard. Study Design: Cross-sectional validation study. Duration and Place of Study: The study was conducted from July 2024 to January 2025 at the Department of Radiology, Shaikh Zayed Hospital, Lahore. Methodology: A total of 130 patients aged 18–60 years, presenting with suspected rotator cuff tears, were enrolled. Ultrasound was performed using a 10 MHz linear probe, and MRI was conducted on a 1.5T machine. Full- and partial-thickness tears were diagnosed based on established imaging criteria. Metrics such as sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the overall effectiveness of ultrasound in diagnosis were assessed. Results: The mean age of patients was 47.32 ± 7.06 years, with 70% male representation and right-sided tears being more prevalent (73.1%). Ultrasound demonstrated a sensitivity of 94%, specificity of 91%, and diagnostic accuracy of 92%. Conclusion: Ultrasound is a reliable, cost-effective diagnostic modality for rotator cuff tears, with accuracy comparable to MRI.